The interplay of common genetic variants NRG1 rs2439302 and RET rs2435357 increases the risk of developing Hirschsprung’s disease - Chi, Shuiqing; Li, Shuai; Cao, Guoqing; Guo, Jialing; Han, Yunqiao; Zhou, Yun; Zhang, Xi; Li, Yibo; Luo, Zhibin; Li, Xiangyang; Rong, Liying; Zhang, Mengxin; et al. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: As a congenital and genetically related disease, many single nucleotide polymorphisms (SNPs) have been reported to be associated with the risk of HSCR. Our previous research showed that SNP rs2439302 (NRG1) interacted with rs2435357 (RET) to increase the risk of HSCR development. However, the underlying molecular mechanism is still not well understood. Methods: SNP rs2439302 (NRG1) and rs2435357 (RET) were genotyped in 470 HSCR cases. The expression of NRG1 and RET was investigated in the colon of HSCR patients. Knockdown of the NRG1 and RET homologs was performed in zebrafish to investigate their synergistic effect on ENS development. The effect of SNP rs2439302 and rs2435357 polymorphism on neuron proliferation, migration, and differentiation were investigated in SHSY-5Y cells and IPSCs. Results: Significant downregulation of NRG1 and RET expression was noticed in the aganglionic segment of HSCR patients and SHSY-5Y cells with rs2439302 GG/rs2435357 TT genotype. NRG1 and RET double mutants caused the most severe reduction in enteric neuron numbers than NRG1 single mutant or RET single mutant in the hindgut of zebrafish. SHSY-5Y cells and IPSCs with rs2439302 GG/rs2435357 TT genotype exhibited a decreased proliferative, migration, and differentiative capacity. CTCF showed a considerably higher binding ability to SNP rs2439302 CC than GG. NRG1 reduction caused a further decrease in SOX10 expression via the PI3K/Akt pathway, which regulates RET expression by directly binding to rs2435357. Discussion: SNP rs2439302 (NRG1) GG increases the risk of developing HSCR by affecting the binding of transcription factor CTCF and interacting with rs2435357 (RET) to regulate RET expression via the PI3K/Akt/SOX10 pathway.